Synthesis of 2‐Nitrothiophenes via Tandem Henry Reaction and Nucleophilic Substitution on Sulfur from β‐Thiocyanatopropenals. (2nd January 2019) - Rong, Lin; Shen, Yingxia; Xiong, Guoxi; Gong, Yuefa
Abstract : A new synthetic route of 2‐nitrothiophenes was described through a tetra‐ n ‐butylammonium fluoride‐promoted or diisopropylethylamine‐promoted tandem Henry reaction and nucleophilic substitution of nitromethane with 3‐thiocyanatopropenals, which were conveniently prepared by the replacement reaction of 3‐chloropropenals with potassium thiocyanate under a mild acidic condition. Abstract :